Utility of TWEAK to assess neuropsychiatric disease activity in systemic lupus erhytematosus. (April 2016) - Fragoso-Loyo, H; Atisha-Fregoso, Y; Nuñez-Alvarez, C A; Llorente, L
Objective: The purpose of this study was to assess the utility of tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) in serum and cerebrospinal fluid (CSF) as a biomarker in neuropsychiatric systemic lupus erythematosus (NPSLE). Methods: Thirty three NPSLE patients were evaluated at hospitalization and six months later. As controls, five SLE patients with septic meningitis, 51 hospitalized SLE patients without a history of neuropsychiatric (NP) manifestations and without infections, 16 SLE patients without NP manifestations (surgical-SLE), four patients with primary neuropsychiatric disorders, and 25 patients with non-autoimmune diseases were also studied. Serum and CSF samples were drawn at hospitalization, except non-NPSLE patients, in whom only serum was studied, and six months later in 19 NPSLE and 27 non-NPSLE patients. Serum and CSF TWEAK levels were measured by ELISA; values are expressed in pg/mL. Results: The mean ± SD age of NPSLE patients was 31 ± 13.1 years, which was similar across study groups ( p  = 0.54). TWEAK levels in serum were not different across the study groups. In CSF, TWEAK levels were higher in NPSLE, surgical-SLE and primary neuropsychiatric groups than in non-autoimmune patients: median (IQR) 159.2 (94.1–374.9), 172.3 (125.3–421.9), 371.3 (143–543) vs 122.1 (76.1–212.4), respectively; all p  < 0.05. Six months later, when the neuropsychiatric manifestations were clinically in remission, serum or CSF TWEAK did not vary from baseline in NPSLE patients. Conclusions: TWEAK levels are slightly elevated in CSF in SLE patients compared with non-autoimmune controls, irrespective of the presence of NP manifestations. TWEAK levels in serum and CSF do not seem to be a useful biomarker of CNS involvement in SLE.